Development of Student Worksheets Based on Project-Based Learning in IPAS (Science and Social Studies) Learning at Elementary School - Susanti, Dini; Septiana, Vini Wela; Kharisma, Inggria; Ekawati, Ridania; Wahyuni, Yulia Septi; Syukri, Muhammad; Naldi, Jepri; Nabillah, Eka Putri (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
AbstractThis research was motivated by several issues, such as public school teachers rarely assigning project or group tasks, and the student worksheets (LKPD) used in schools were considered less appealing to students, especially in terms of visual design. The purpose of this research is to develop a Project Based Learning (PjBL)-based LKPD for IPAS (Science and Social Studies Integration) learning in Grade IV of Elementary School that meets the criteria of being valid, practical, and effective.The method used in this study is Research and Development (RD) using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The product was validated by experts using a validity questionnaire. The practicality aspect was assessed using a questionnaire completed by teachers, and effectiveness was evaluated through a questionnaire filled out by students.The results of the development of the Project Based Learning (PjBL)-based Student Worksheet (LKPD) showed a validity score of 81%, categorized as very valid. The practicality score was 94%, categorized as very practical. The effectiveness score was 88%, categorized as very effective. Therefore, it can be concluded that the PjBL-based LKPD is valid, practical, and effective, and can be used by students.Keywords: LKPD, PjBL, ADDIE